The Development of an Instructional Model Based on Social Cognitive Theory to Enhance English Listening and Speaking Skills for Grade 6 Students in Small Size Schools - Sukanya Thaosiri; Jiraporn Chano (Journal of Educational Issues, 2024)
This research aimed to study the basic information and needs for the development of an instructional model based on social cognitive theory to enhance English listening and speaking skills for grade 6 students in small size schools, develop the model, and study the results of implementation. The sample group was 8 students of Ratruamrangrat (Kamjad Upatham) School in the 2nd semester of the academic year 2019, selected by cluster random sampling. The research instruments were a questionnaire for students, an interviewing form for teachers, a learning management manual, lesson plans, English listening and speaking tests, and English listening and speaking skills achievement test. The findings revealed that the total level of students’ English listening and speaking skills enhancement was low, while teachers lacked confidence and techniques in teaching English for communication. The developed model consisted of 6 components including principles, objectives, syntax, principle of reaction, and support system, respectively. The results of implementation showed students’ a significant improvement in the overall and each English listening and speaking skills. Their learning achievement for both English listening and speaking skills after learning through the developed model was higher than that assessed before learning through the model at the statistically significant level of .05.